Addressing Global Health, Development, and Social Inequalities through Research and Policy Analyses: the International Journal of MCH and AIDS - Romuladus E. Azuine, DrPH, RN; Gopal K. Singh, PhD (Global Health and Education Projects, Inc., 2012)
One year after the birth of the International Journal of MCH and AIDS (IJMA), we continue to share the passion to document, and shine the light on the myriads of global health issues that debilitate developing countries.Although the focus of IJMA is on the social determinants of health and disease as well as on the disparities in the burden of communicable and non-communicable diseases affecting infants, children, women, adults, and families in developing countries, we would like to encourage our fellow researchers and policy makers in both the developing and developed countries to consider submitting work that examines cross-national variations in heath and social inequalities.Such a global focus allows us to identify and understand social, structural, developmental, and health policy determinants underlying health inequalities between nations.Global assessment of health and socioeconomic patterns reaffirms the role of broader societal-level factors such as human development, gender inequality, gross national product, income inequality, and healthcare infrastructure as the fundamental determinants of health inequalities between nations.This is also confirmed by our analysis of the WHO data that shows a strong negative association between levels of human development and infant and maternal mortality rates.Focusing on socioeconomic, demographic, and geographical inequalities within a developing country, on the other hand, should give us a sense of how big the problem of health inequity is within its own borders.Such an assessment, then, could lead to development of policy solutions to tackle health inequalities that are unique to that country.